2013
DOI: 10.3354/meps10591
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors that influence the distribution, size, and biotic relationships of the Christmas tree coral Antipathes dendrochristos in the Southern California Bight

Abstract: The Christmas tree coral Antipathes dendrochristos is a recently discovered black coral species that represents a habitat associated with numerous sensitive taxa in the Southern California Bight. We evaluated whether broad-scale oceanographic features influence coral density and size by selecting from among generalized additive models (for density) and generalized linear models (for size) that represented competing hypotheses. We constructed models to predict coral density and size using depth, seafloor slope,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Cross Seamount, the oldest site, with a mature gold coral population, is also the southernmost, sharing the same environment as sites with fewer corals (Westpac, Makapuu, Keahole). The role of environmental variables including current flow, particulate fluxes, and productivity (Huff et al 2013) in this depth range is not known. However, data loggers have monitored temperature in coral beds (5+ yr) across the archipelago and found it stable, varying between 8 and 11°C (Table 1) (Parrish & Roark 2009).…”
Section: Community Patterns and The Process Of Successionmentioning
confidence: 99%
“…Cross Seamount, the oldest site, with a mature gold coral population, is also the southernmost, sharing the same environment as sites with fewer corals (Westpac, Makapuu, Keahole). The role of environmental variables including current flow, particulate fluxes, and productivity (Huff et al 2013) in this depth range is not known. However, data loggers have monitored temperature in coral beds (5+ yr) across the archipelago and found it stable, varying between 8 and 11°C (Table 1) (Parrish & Roark 2009).…”
Section: Community Patterns and The Process Of Successionmentioning
confidence: 99%
“…Models developed at finer scales are perhaps more useful to identify areas that could be protected from anthropogenic practices that may potentially damage these fragile DSCS taxa (Rengstorf et al, 2013;Gullage et al, 2017;Sundahl et al, 2020). For example, Huff et al (2013) found that the distribution of the Christmas tree coral in the SCB (Antipathes dendrochristos) was positively affected by a combination of persistently high surface productivity, water current velocity and direction near the seafloor, warmer temperature and shallow depth. Developing similar distribution maps for the other DSCS taxa associated with demersal fishes would be invaluable to fisheries managers seeking to protect these vulnerable fish habitats as they seek to rebuild overfished populations (Rosenberg et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that some of the other DSCS taxa that were near the top of the gradient forest analysis (e.g., Pennatulacea and Antipathes dendrochristos) also may have important habitat roles for other taxa that were not included in our logistic regression models. Habitats with persistent localized upwelling resulting from complex seafloor topography are areas where Antipathes dendrochristos are denser (Huff et al, 2013), and also may comprise the most important benthic habitats for other DSCS and fishes in the SCB.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, L. pertusa reefs off Norway occur in waters as shallow as 50 m; with it being impossible to determine whether temperature (up to 10 • C) or salinity (down to 32) limit the upper bathymetrical distribution (Mortensen et al, 2001). Therefore, assertions on the potential controls of deepsea species distributions should be taken with caution (Huff et al, 2013). In addition, the relative importance of these factors varies between taxa and regions, but also with the spatial and temporal window of observation (Buhl-Mortensen et al, 2015;Radice et al, 2016).…”
Section: Water Mass Properties As Drivers Of Deep-sea Biodiversity Anmentioning
confidence: 99%